Griseofulvin Derivatives: Synthesis, Molecular Docking and Biological Evaluation - Kartsev, Victor; Geronikaki, Athina; Petrou, Anthi; Lichitsky, Boris; Kostic, Marina; Smiljkovic, Marija; Soković, Marina; Sirakanyan, Samvel (Current Topics in Medicinal Chemistry, 2019)
Background: Griseofulvin - a mold metabolite produced by Penisilium griseofulvum is known as an antifungal drug. Objective: Thus, the goal of this paper is the design and synthesis of new griseofulvin derivatives and evaluation of their antifungal activity. Methods: Forty-two new compounds were synthesized using classical methods of organic synthesis and evaluated for their antimicrobial activity by microdilution method. Results: All forty-two new compounds exhibited very good activity against eight tested micromycetes with MIC ranging from 0.0075-0.055 mg/ml and MFC from 0.02-024 mg/ml. All compounds exhibited better activity than reference drugs ketoconazole (7-42 times) and bifonazole (3-16 fold). The most promising was compound 15. The most sensitive fungal was found to be T. viride, while the most resistant, as was expected, was A. fumigatus. It should be mentioned that most of compounds exhibited better activity than griseofulvin. The molecular docking studies revealed that the most active compound have the same hydrophobic and H-bonding interactions with Thr276 residue observed for griseofulvin forming 3 hydrogen bonds while griseofulvin only one. In general, the molecular docking results coincide with experimental. Conclusion: Forty-two giseofulvin derivatives were designed, synthesized and evaluated for antimicrobial activity. These derivatives revealed good antifungal activity, better than reference drugs ketoconazole, bifonazole, and griseofulvin as well.
Keywords: Bifonazole